Optimization of Blue Light Patrol by the Turjagwali Traffic Units to Reduce Traffic Accidents in the Jurisdiction of the Pemalang Resort Police - Rianto, Ajeng Ayu (Advances in Police Science Research Journal, 2024)
The high number of traffic accidents is one of the problems that has always been the main highlight, this happens in almost all regions of Indonesia, especially those with heavy traffic flow. This also happens in the Pemalang Regency area, traffic accidents that occur are increasing from time to time, especially at night despite efforts from the Turjagwali Unit of the Pemalang Police Station through Blue Light Patrol activities. For this reason, the problem in this final project is why the implementation of the Blue Light Patrol Unit Turjagwali Satlantas to reduce traffic accidents in the jurisdiction of Pemalang Police Station has not been optimal. The purpose of this paper is to describe the implementation of the Turjagwali Blue Light Patrol Unit and the involvement of the community to reduce traffic accidents in the jurisdiction of Pemalang Police Station. This final project uses a qualitative approach. In data validity, the author uses data triangulation, while for data analysis techniques use data reduction, data presentation, and conclusions. In discussing the issue, using SWOT analysis theory to analyze factors that affect the application of Blue Light Patrol and management theory to analyze the application of Blue Light Patrol to reduce traffic accidents in the jurisdiction of Pemalang Police Station. As a result of the writing done by the author, there are still many shortcomings and findings regarding the application of Blue Light Patrol. Some of these findings include the lack of development education carried out by members, the wide scope of patrol areas and the lack of community involvement in it. The author provides several problem solutions that can be done, including bringing in relevant resource persons related to checking sarpras regularly, adding knowledge to members and maximizing reports on the results of activities. The suggestion proposed by the author is to cooperate with relevant resource persons related to educational materials for member development and also involve the role of the community in activities as a basis or material for work evaluation.